Preservation of cultural heritage in Tibet - Li, Yin (2020)
Tholing Monastery is one of the most important religious monuments in western Tibet, and its murals show the greatest artistic achievement of the Tibetans in the cultural and aesthetic context in the two different periods of Tibetan history. This article first introduces the historical context of this monument, indicating its importance in the development of Tibetan history. Secondly, both the historical and artistic value of the murals of the Tholing Monastery are explained and it is suggested that this monument deserves more attention in preservation and research, and should be included in the UNESCO World Heritage List. Finally, it is considered that the tourist use of the Tholing Monasteries and its Buddhist frescoes could contribute in the future to promote the tourism industry in that area.